Comprehensive care of a patient with obesity of BMI >70 kg/m 2 - Shaila Kabir; ABM Tofazzal Hossain; Sadia Choudhury Shimmi; Choo, Si Jie (BMJ Publishing Group, 2020)
A 31-year-old woman, with a body mass index of 70.31 kg/m2, presented with progressive worsening of dyspnoea for 3 days. She had multiple comorbidities, including obesity hypoventilation syndrome. The patient developed type II respiratory failure with respiratory acidosis along with multiorgan failure. She was intubated and put on a mechanical ventilator and treated with intravenous diuretics, subcutaneous low-molecular-weight heparin and other supportive measures. Later, she was on noninvasive, continuous positive airway pressure ventilation overnight. She was prescribed a very-low-calorie diet along with physiotherapy and exercise. The patient underwent bariatric surgery 2 months after resolution of acute illness. Ten months after surgery, her body weight reduced from 180 kg to 121 kg, and her general condition improved. Successful management before and after surgical intervention depends on multidisciplinary teamwork, which includes the dietician, physiotherapist, endocrinologist, pulmonologist, nursing care and other supportive care.